Pik Botha and his times, Theresa Papenfus: book review - Neethling, Theo (Faculty of Law, University of the Free State, 2011)
Abstract not available
Theresa Papenfus, Pik Botha and his times. Pretoria: Litera Publications, 2010. ISBN: 978-1-920188-34-4.
Keywords: Book reviews